Indeterminacy conditions for the matrix Nevanlinna-Pick problem and rational matrix functions of the first and second kind - Dyukarev, Yu. M. (Methods of Functional Analysis and Topology, 2022)
We obtain new indeterminacy conditions for the matrix Nevanlinna-Pick interpolation problem. These conditions are formulated in terms of the convergence of two matrix series. The elements of these series are rational matrix functions of the first and second kind. Отримано нові умови невизначеності для матричної інтерполяційної задачі Неванлінни-Піка. Ці умови формулюється в термінах збіжності двох матричних рядів. Елементами цих рядів є раціональні матриць-функції першого і другого роду.